KEMAMPUAN MEMODIFIKASI DOUSHI PADA SISWA KELAS XII IPS 1 SMA PGRI 4 PADANG - indah puspita; - Refnaldi; hendri zalman (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2018)
This study discussed the students ability of modifiying doushi class XII IPS 1 SMA PGRI 4 Padang. The purpose of this study is to find out how to modify  doushi ability. This type of research is quantitative research with descriptive methods. The total population were 120 students. The sample in this research was class XII IPS 1 SMA PGRI 4 Padang in total 32 students who were determined by using proposive sampling technique. The data of this research was the score of modified Doushi test results . Based on the results of the research tests carried out , the following points can be concluded. First, the modification ability of doushi students of class XII IPS 1 at SMA PGRI 4 Padang with an average score of 50,20. Second, from the three indicators tested, it can be concluded that the ability of doushi students of class XII IPS 1 in SMA PGRI 4 Padang did not have the strongest indicator, because in the three indicators there were almost the　same average scores on indicator I (identifying doushi in the form of ー た past　form ) with an average value of 50.93 and for indicator II (Identifying doushi in the　form ―ていますongoing form ) with an average value of 44.43. Third ( identifying doushi in the form―ます the form will be) with the value i averaging 55,37.The four is  doushi abilities included in the classification class are lacking.Keyword: Ability, Modify Doushi